The Dutch Revolt and Catholic exile in Reformation Europe - Janssen, Geert H. (Cambridge University Press, 2014)
"The present study seeks to probe the formative impact of exile on changing Catholic identities, both in the northern and in the southern Netherlands. More specifically, it will argue that many displaced Catholics became receptive to militant strands of Catholicism during their years in foreign safe havens. Local media, clerical leadership and forms of sociability facilitated and shaped this process of religious radicalisation among Catholic expatriates. When the changing course of the war allowed the exiles to return home, these spiritually reborn men and women promulgated their radical beliefs in areas recovered by the Habsburg monarchy"--